Generalized regular fuzzy biclosure spaces - Tapi, UD; Navalakhe, R (Kathmandu University Journal of Science Engineering and Technology, 2013)
The purpose of this paper is to introduce new notion of regular fuzzy biclosure space called generalized regular fuzzy biclosure space and investigate some of their characterizations. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 43-47 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7324